2020
DOI: 10.3934/microbiol.2020020
|View full text |Cite
|
Sign up to set email alerts
|

Breakthroughs in the discovery and use of different peroxidase isoforms of microbial origin

Abstract: Peroxidases are classified as oxidoreductases and are the second largest class of enzymes applied in biotechnological processes. These enzymes are used to catalyze various oxidative reactions using hydrogen peroxide and other substrates as electron donors. They are isolated from various sources such as plants, animals and microbes. Peroxidase enzymes have versatile applications in bioenergy, bioremediation, dye decolorization, humic acid degradation, paper and pulp, and textile industries. Besides, peroxidases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Dyp is another heme-containing peroxidase that can degrade various dyes, lignin-related compounds, and multiple mycotoxins and has drawn tremendous interest for biotechnological applications [ 25 ]. Therefore, the Bs Dyp was chosen as the first target protein to evaluate the potential of Ec -M13 strain, the high-heme-producing E. coli recombinant, for heme protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Dyp is another heme-containing peroxidase that can degrade various dyes, lignin-related compounds, and multiple mycotoxins and has drawn tremendous interest for biotechnological applications [ 25 ]. Therefore, the Bs Dyp was chosen as the first target protein to evaluate the potential of Ec -M13 strain, the high-heme-producing E. coli recombinant, for heme protein synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Peroxidase (POD) is one of the most widely used enzymes in biotechnological research, which can be ubiquitously found in animals, plants, and microorganisms. [103,104] It catalyzes various oxidation reactions by using H 2 O 2 or other substrates as electron donors. Following the first discovery of the intrinsic PODlike activity of Fe 3 O 4 nanoparticles, the science of nanozymes has blossomed considerably.…”
Section: Peroxidase-like Activitymentioning
confidence: 99%
“…Mn is required to build reactive centres in manganese peroxidase enzymes. These enzymes are produced by bacteria and fungi commonly cited in plastic studies (Twala et al, 2020), and have been shown to have an affinity for plastics (Enyoh et al, 2022), and are even suggested as potentially degradative towards PE (Twala et al, 2020).…”
Section: Mineral and Metal Association With Plasticmentioning
confidence: 99%